Corporate Governance and Earnings Management: Insights from Jakarta Islamic Index Firms - Wicaksono, Panji; Andriansyah, Yuli; Hattabou, Anas (Universitas Islam Indonesia, 2023)
This study investigates the impact of corporate governance mechanisms, firm size, and market share on earnings management in companies listed on the Jakarta Islamic Index (JII) from 2014 to 2017. With a focus on the ethical framework of Islamic finance, the research aims to understand how governance structures mitigate opportunistic financial behaviors and promote transparency. The study employs a quantitative research design, using secondary data from audited financial reports of JII-listed firms. Multiple regression analysis was applied to assess the relationships between discretionary accruals, as a proxy for earnings management, and independent variables such as audit committee expertise, managerial and institutional ownership, board independence, firm size, and market share. The findings reveal that robust governance mechanisms, including well-composed audit committees, higher managerial and institutional ownership, and independent boards, significantly reduce earnings management. Larger firms and those subjected to high-quality audits also exhibit lower levels of financial manipulation. However, market share does not show a significant impact on earnings management, suggesting the dominance of governance and external scrutiny over competitive positioning in shaping reporting behaviors. These results underscore the interplay between governance practices and ethical financial reporting within the JII context. This research contributes to the broader literature on corporate governance and earnings management by offering insights specific to Islamic financial principles. The findings have practical implications for policymakers and practitioners, emphasizing the importance of strengthening governance frameworks to enhance corporate accountability and stakeholder trust. Further research could explore governance dynamics across diverse financial systems to build a comprehensive understanding of their global implications.